Internal
problem
ID
[8742] Book
:
Own
collection
of
miscellaneous
problems Section
:
section
1.0 Problem
number
:
31 Date
solved
:
Monday, January 27, 2025 at 04:46:03 PM CAS
classification
:
[[_homogeneous, `class A`], _rational, _Riccati]
An ode of the form \(y' = \frac {M(x,y)}{N(x,y)}\) is called homogeneous if the functions \(M(x,y)\) and \(N(x,y)\) are both homogeneous
functions and of the same order. Recall that a function \(f(x,y)\) is homogeneous of order \(n\) if
\[ f(t^n x, t^n y)= t^n f(x,y) \]
In this
case, it can be seen that both \(M=5 x^{2}-x y +y^{2}\) and \(N=x^{2}\) are both homogeneous and of the same order \(n=2\). Therefore
this is a homogeneous ode. Since this ode is homogeneous, it is converted to separable ODE
using the substitution \(u=\frac {y}{x}\), or \(y=ux\). Hence
We now need to find the singular solutions, these are found by finding for
what values \(g(u)\) is zero, since we had to divide by this above. Solving \(g(u)=0\) or
\[
u^{2}-2 u +5=0
\]
for \(u \left (x \right )\) gives
\begin{align*} u \left (x \right )&=1-2 i\\ u \left (x \right )&=1+2 i \end{align*}
Now we go over each such singular solution and check if it verifies the ode itself and
any initial conditions given. If it does not then the singular solution will not be
used.
Therefore the solutions found are
\begin{align*}
\frac {\arctan \left (\frac {u \left (x \right )}{2}-\frac {1}{2}\right )}{2} &= \ln \left (x \right )+c_1 \\
u \left (x \right ) &= 1-2 i \\
u \left (x \right ) &= 1+2 i \\
\end{align*}
Solving for \(u \left (x \right )\) gives
\begin{align*}
u \left (x \right ) &= 1-2 i \\
u \left (x \right ) &= 1+2 i \\
u \left (x \right ) &= 1+2 \tan \left (2 \ln \left (x \right )+2 c_1 \right ) \\
\end{align*}
Converting \(u \left (x \right ) = 1-2 i\) back to \(y\) gives
\begin{align*} y = \left (1-2 i\right ) x \end{align*}
Converting \(u \left (x \right ) = 1+2 i\) back to \(y\) gives
\begin{align*} y = \left (1+2 i\right ) x \end{align*}
We now need to find the singular solutions, these are found by finding for
what values \(g(u)\) is zero, since we had to divide by this above. Solving \(g(u)=0\) or
\[
u^{2}-2 u +5=0
\]
for \(u \left (x \right )\) gives
\begin{align*} u \left (x \right )&=1-2 i\\ u \left (x \right )&=1+2 i \end{align*}
Now we go over each such singular solution and check if it verifies the ode itself and
any initial conditions given. If it does not then the singular solution will not be
used.
Therefore the solutions found are
\begin{align*}
\frac {\arctan \left (\frac {u \left (x \right )}{2}-\frac {1}{2}\right )}{2} &= \ln \left (x \right )+c_1 \\
u \left (x \right ) &= 1-2 i \\
u \left (x \right ) &= 1+2 i \\
\end{align*}
Solving for \(u \left (x \right )\) gives
\begin{align*}
u \left (x \right ) &= 1-2 i \\
u \left (x \right ) &= 1+2 i \\
u \left (x \right ) &= 1+2 \tan \left (2 \ln \left (x \right )+2 c_1 \right ) \\
\end{align*}
Converting \(u \left (x \right ) = 1-2 i\) back to \(y\) gives
\begin{align*} y = \left (1-2 i\right ) x \end{align*}
Converting \(u \left (x \right ) = 1+2 i\) back to \(y\) gives
\begin{align*} y = \left (1+2 i\right ) x \end{align*}
An ode of the form \(Y' = \frac {M(X,Y)}{N(X,Y)}\) is called homogeneous if the functions \(M(X,Y)\) and \(N(X,Y)\) are both homogeneous
functions and of the same order. Recall that a function \(f(X,Y)\) is homogeneous of order \(n\) if
\[ f(t^n X, t^n Y)= t^n f(X,Y) \]
In this
case, it can be seen that both \(M=5 X^{2}-X Y +Y^{2}\) and \(N=X^{2}\) are both homogeneous and of the same order \(n=2\). Therefore
this is a homogeneous ode. Since this ode is homogeneous, it is converted to separable ODE
using the substitution \(u=\frac {Y}{X}\), or \(Y=uX\). Hence
We now need to find the singular solutions, these are found by finding for
what values \(g(u)\) is zero, since we had to divide by this above. Solving \(g(u)=0\) or
\[
u^{2}-2 u +5=0
\]
for \(u \left (X \right )\) gives
\begin{align*} u \left (X \right )&=1-2 i\\ u \left (X \right )&=1+2 i \end{align*}
Now we go over each such singular solution and check if it verifies the ode itself and
any initial conditions given. If it does not then the singular solution will not be
used.
Therefore the solutions found are
\begin{align*}
\frac {\arctan \left (\frac {u \left (X \right )}{2}-\frac {1}{2}\right )}{2} &= \ln \left (X \right )+c_1 \\
u \left (X \right ) &= 1-2 i \\
u \left (X \right ) &= 1+2 i \\
\end{align*}
Solving for \(u \left (X \right )\) gives
\begin{align*}
u \left (X \right ) &= 1-2 i \\
u \left (X \right ) &= 1+2 i \\
u \left (X \right ) &= 1+2 \tan \left (2 \ln \left (X \right )+2 c_1 \right ) \\
\end{align*}
Converting \(u \left (X \right ) = 1-2 i\) back to \(Y \left (X \right )\) gives
\begin{align*} Y \left (X \right ) = \left (1-2 i\right ) X \end{align*}
Converting \(u \left (X \right ) = 1+2 i\) back to \(Y \left (X \right )\) gives
\begin{align*} Y \left (X \right ) = \left (1+2 i\right ) X \end{align*}
We now need to find the singular solutions, these are found by finding for
what values \(g(u)\) is zero, since we had to divide by this above. Solving \(g(u)=0\) or
\[
u^{2}-2 u +5=0
\]
for \(u \left (x \right )\) gives
\begin{align*} u \left (x \right )&=1-2 i\\ u \left (x \right )&=1+2 i \end{align*}
Now we go over each such singular solution and check if it verifies the ode itself and
any initial conditions given. If it does not then the singular solution will not be
used.
Therefore the solutions found are
\begin{align*}
\frac {\arctan \left (\frac {u \left (x \right )}{2}-\frac {1}{2}\right )}{2} &= \ln \left (x \right )+c_1 \\
u \left (x \right ) &= 1-2 i \\
u \left (x \right ) &= 1+2 i \\
\end{align*}
Solving for \(u \left (x \right )\) gives
\begin{align*}
u \left (x \right ) &= 1-2 i \\
u \left (x \right ) &= 1+2 i \\
u \left (x \right ) &= 1+2 \tan \left (2 \ln \left (x \right )+2 c_1 \right ) \\
\end{align*}
Converting \(u \left (x \right ) = 1-2 i\) back to \(y\) gives
\begin{align*} \frac {y}{x} = 1-2 i \end{align*}
Converting \(u \left (x \right ) = 1+2 i\) back to \(y\) gives
Substituting the above solution in the anstaz (1E,2E) (using \(1\) as arbitrary value for any
unknown in the RHS) gives
\begin{align*}
\xi &= x \\
\eta &= y \\
\end{align*}
Shifting is now applied to make \(\xi =0\) in order to simplify the rest of
the computation
\begin{align*} \eta &= \eta - \omega \left (x,y\right ) \xi \\ &= y - \left (\frac {5 x^{2}-x y +y^{2}}{x^{2}}\right ) \left (x\right ) \\ &= \frac {-5 x^{2}+2 x y -y^{2}}{x}\\ \xi &= 0 \end{align*}
The next step is to determine the canonical coordinates \(R,S\). The canonical coordinates map \(\left ( x,y\right ) \to \left ( R,S \right )\)
where \(\left ( R,S \right )\) are the canonical coordinates which make the original ode become a quadrature and
hence solved by integration.
The characteristic pde which is used to find the canonical coordinates is
The above comes from the requirements that \(\left ( \xi \frac {\partial }{\partial x} + \eta \frac {\partial }{\partial y}\right ) S(x,y) = 1\). Starting with the first pair of ode’s in (1)
gives an ode to solve for the independent variable \(R\) in the canonical coordinates, where \(S(R)\). Since
\(\xi =0\) then in this special case
\begin{align*} R = x \end{align*}
\(S\) is found from
\begin{align*} S &= \int { \frac {1}{\eta }} dy\\ &= \int { \frac {1}{\frac {-5 x^{2}+2 x y -y^{2}}{x}}} dy \end{align*}
We now need to express the RHS as function of \(R\) only. This is done by solving for \(x,y\) in terms of
\(R,S\) from the result obtained earlier and simplifying. This gives
The above is a quadrature ode. This is the whole point of Lie symmetry method. It converts
an ode, no matter how complicated it is, to one that can be solved by integration when the
ode is in the canonical coordiates \(R,S\).
Since the ode has the form \(\frac {d}{d R}S \left (R \right )=f(R)\), then we only need to integrate \(f(R)\).
This is Euler second order ODE. Let the solution be \(u = x^r\), then \(u'=r x^{r-1}\) and \(u''=r(r-1) x^{r-2}\). Substituting these back
into the given ODE gives
\[ x^{2}(r(r-1))x^{r-2}+3 x r x^{r-1}+5 x^{r} = 0 \]
Using Euler relation, the expression \(c_1 e^{i A}+ c_2 e^{-i A}\) is transformed to \( c_1 \cos A+ c_1 \sin A\) where the constants are free to
change. Applying this to the above result gives
`Methodsfor first order ODEs:---Trying classification methods ---tryinga quadraturetrying1st order lineartryingBernoullitryingseparabletryinginverse lineartryinghomogeneous types:tryinghomogeneous D<-homogeneous successful`